Bailey and love's short practice of surgery. 27th edition. the collector$1 (Bs edition /s - McCaskie, Andrew (Andrew W.); O'Connell, P Ronan; Williams, Norman; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
Bailey and Love is the world famous textbook of surgery. Its comprehensive coverage includes the scientific basis of surgical practice, investigation, diagnosis, and pre-operative care. Trauma and Orthopaedics are included, as are the subspecialties of plastic and reconstructive, head and neck, cardiothoracic and vascular, abdominal and genitourinary surgery. The user-friendly format includes photographs, line diagrams, learning objectives, summary boxes, biographical footnotes, memorable anecdotes and full-colour page design. This book's reputation for unambiguous advice make it the first point of reference for student and practising surgeons worldwide.
part 1 Part 1: Basic Principles -- chapter 1 Metabolic response to injury -- chapter 2 Shock and blood transfusion -- chapter 3 Wounds, healing and tissue repair -- chapter 4 Tissue engineering and regeneration -- chapter 5 Surgical infection -- chapter 6 Tropical infections and infestations -- chapter 7 Basic surgical skills and anastomoses -- chapter 8 Principles of laparoscopic and robotic surgery -- chapter 9 Principles of paediatric surgery -- chapter 10 Principles of oncology -- chapter 11 Surgical audit and research -- chapter 12 Surgical ethics and law -- chapter 13 Human factors, patient safety and quality improvement -- part 2 Part 2: Investigation and Diagnosis -- chapter 14 Diagnostic imaging -- chapter 15 Gastrointestinal Endoscopy -- chapter 16 Tissue and Molecular Diagnosis -- part 3 Part 3: Perioperative Care -- chapter 17 Preoperative Care Including the High-Risk Surgical Patient -- chapter 18 Anaesthesia and pain relief -- chapter 19 Nutrition and fluid therapy -- chapter 20 Postoperative care -- chapter 21 Day case surgery -- part 4 Part 4: Trauma -- chapter 22 Introduction to trauma -- chapter 23 Early assessment and management of severe trauma -- chapter 24 Traumatic brain injury -- chapter 25 Neck and Spine -- chapter 26 Maxillofacial Trauma -- chapter 27 Torso trauma -- chapter 28 Extremity trauma -- chapter 29 Disaster surgery -- chapter 30 Conflict surgery -- part 5 Part 5: Elective Orthopaedics -- chapter 31 History taking and clinical examination in musculoskeletal disease -- chapter 32 Sports medicine and sports injuries -- chapter 33 The spine -- chapter 34 Upper limb -- chapter 35 Hip and knee -- chapter 36 Foot and ankle -- chapter 37 Musculoskeletal tumours -- chapter 38 Infection of the bones and joints -- chapter 39 Paediatric orthopaedics -- part 6 Part 6: Skin and Subcutaneous Tissue -- chapter 40 Skin and subcutaneous tissue -- chapter 41 Burns -- chapter 42 Plastic and reconstructive surgery -- part 7 Part 7 Head and Neck -- chapter 43 Cranial Neurosurgery -- chapter 44 The eye and orbit -- chapter 45 Cleft lip and palate: developmental abnormalities of the face, mouth and jaws -- chapter 46 The ear, nose and sinuses -- chapter 47 Pharynx, Larynx and Neck -- chapter 48 Oral cavity malignancy -- chapter 49 Disorders of the salivary glands -- part 8 Part 8 Breast and endocrine -- chapter 50 The thyroid gland -- chapter 51 The parathyroid glands -- chapter 52 The adrenal glands and other abdominal endocrine disorders -- chapter 53 The breast -- part 9 Part 9 Cardiothoracic -- chapter 54 Cardiac surgery -- chapter 55 The thorax -- part 10 Part 10 Vascular -- chapter 56 Arterial disorders -- chapter 57 Venous disorders -- chapter 58 Lymphatic disorders -- part 11 Part 11 Abdominal -- chapter 59 History and Examination of the Abdomen -- chapter 60 Abdominal wall, hernia and umbilicus -- chapter 61 The peritoneum, omentum, mesentery and retroperitoneal space -- chapter 62 The oesophagus -- chapter 63 Stomach and duodenum -- chapter 64 Bariatric and metabolic surgery -- chapter 65 The liver -- chapter 66 The spleen -- chapter 67 The Gallbladder and Bile Ducts -- chapter 68 The pancreas -- chapter 69 The Small Intestine -- chapter 70 The large intestine -- chapter 71 Intestinal obstruction -- chapter 72 The vermiform appendix -- chapter 73 The rectum -- chapter 74 The anus and anal canal -- part 12 Part 12 Genitourinary -- chapter 75 Urinary Symptoms and Investigations -- chapter 76 Kidneys and ureters -- chapter 77 The urinary bladder -- chapter 78 The prostate and seminal vesicles -- chapter 79 Urethra and Penis -- chapter 80 Testis and scrotum -- chapter 81 Gynaecology -- part 13 Part 13: Transplantation -- chapter 82 Transplantation.
Keywords: Perioperative Care; Surgery -- Textbooks; Surgery; Surgical Procedures, Operative